Hyperbaric Oxygen Therapy Alleviates Carbon Monoxide Poisoning–Induced Delayed Memory Impairment by Preserving Brain-Derived Neurotrophic Factor–Dependent Hippocampal Neurogenesis. Issue 1 (January 2016) - Liu, Wen-Chung; Yang, San-Nan; Wu, Chih-Wei J.; Chen, Lee-Wei; Chan, Julie Y.H.
Abstract : Objective: To test the hypothesis that hyperbaric oxygen therapy ameliorates delayed cognitive impairment after acute carbon monoxide poisoning by promoting neurogenesis through upregulating the brain-derived neurotrophic factor in the hippocampus. Design: Laboratory animal experiments. Setting: University/Medical center research laboratory. Subjects: Adult, male Sprague-Dawley rats. Interventions: Rats were divided into five groups: (1) non–carbon monoxide-treated control, (2) acute carbon monoxide poisoning, (3) acute carbon monoxide poisoning followed by 7-day hyperbaric oxygen treatment, (4) carbon monoxide + hyperbaric oxygen with additional intracerebroventricular infusion of Fc fragment of tyrosine kinase receptor B protein (TrkB-Fc) chimera, and (5) acute carbon monoxide poisoning followed by intracerebroventricular infusion of brain-derived neurotrophic factor. Acute carbon monoxide poisoning was achieved by exposing the rats to carbon monoxide at 2, 500 ppm for 40 minutes, followed by 3, 000 ppm for 20 minutes. Hyperbaric oxygen therapy (at 2.5 atmospheres absolute with 100% oxygen for 60 min) was conducted during the first 7 days after carbon monoxide poisoning. Recombinant human TrkB-Fc chimera or brain-derived neurotrophic factor was infused into the lateral ventricle via the implanted osmotic minipump. For labeling of mitotic cells in the hippocampus, bromodeoxyuridine was injected into the peritoneal cavity. Distribution of bromodeoxyuridine and two additional adult neurogenesis markers, Ki-67 and doublecortin, in the hippocampus was evaluated by immunohistochemistry or immunofluorescence staining. Tissue level of brain-derived neurotrophic factor was assessed by enzyme-linked immunosorbent assay. Cognitive behavior was evaluated by the use of eight-arm radial maze. Measurements and Main Results: Acute carbon monoxide poisoning significantly suppressed adult hippocampal neurogenesis evident by the reduction in number of bromodeoxyuridine-positive, Ki-67 +, and doublecortin + cells in the subgranular zone of the dentate gyrus. This suppression of adult neurogenesis by the carbon monoxide poisoning was appreciably alleviated by early treatment of hyperbaric oxygen. The hyperbaric oxygen treatment also promoted a sustained increase in hippocampal brain-derived neurotrophic factor level. Blockade of hippocampal brain-derived neurotrophic factor signaling with intracerebroventricular infusion of recombinant human TrkB-Fc chimera significantly blunted the protection by the hyperbaric oxygen on hippocampal neurogenesis; whereas intracerebroventricular infusion of brain-derived neurotrophic factor mimicked the action of hyperbaric oxygen and preserved hippocampal neurogenesis after acute carbon monoxide poisoning. Furthermore, acute carbon monoxide poisoning resulted in a delayed impairment of cognitive function. The hyperbaric oxygen treatment notably restored the cognitive impairment in a brain-derived neurotrophic factor–dependent manner. Conclusions: The early hyperbaric oxygen treatment may alleviate delayed memory impairment after acute carbon monoxide poisoning by preserving adult neurogenesis via an increase in hippocampal brain-derived neurotrophic factor content.